Genetic dyslexia risk variant is related to neural connectivity patterns underlying phonological awareness in children. - Skeide, M. A.; Kirsten, H.; Kraft, I.; Schaadt, G.; Muller, B.; Neef, N.; Brauer, J.; Wilcke, A.; Emmrich, F.; Boltze, J.; Friederici, A. D. (Neuroimage, 2015)
Phonological awareness is the best-validated predictor of reading and spelling skill and therefore highly relevant for developmental dyslexia. Prior imaging genetics studies link several dyslexia risk genes to either brain-functional or brain-structural factors of phonological deficits. However, coherent evidence for genetic associations with both functional and structural neural phenotypes underlying variation in phonological awareness has not yet been provided. Here we demonstrate that rs11100040, a reported modifier of SLC2A3, is related to the functional connectivity of left fronto-temporal phonological processing areas at resting state in a sample of 9- to 12-year-old children. Furthermore, we provide evidence that rs11100040 is related to the fractional anisotropy of the arcuate fasciculus, which forms the structural connection between these areas. This structural connectivity phenotype is associated with phonological awareness, which is in turn associated with the individual retrospective risk scores in an early dyslexia screening as well as to spelling. These results suggest a link between a dyslexia risk genotype and a functional as well as a structural neural phenotype, which is associated with a phonological awareness phenotype. The present study goes beyond previous work by integrating genetic, brain-functional and brain-structural aspects of phonological awareness within a single approach. These combined findings might be another step towards a multimodal biomarker for developmental dyslexia.
Keywords: Awareness/*physiology; Brain Mapping; Child; Diffusion Tensor Imaging; Dyslexia/*genetics/pathology/*physiopathology; Female; Frontal Lobe/pathology/*physiopathology; Genetic Predisposition to Disease; Humans; Magnetic Resonance Imaging; Male; Neural Pathways/pathology/physiopathology; Phonetics; Polymorphism, Single Nucleotide; Psychometrics; Reading; Temporal Lobe/pathology/*physiopathology